Selection against spermatozoa with fragmented DNA after postovulatory mating depends on the type of damage - Pintado Belén; Gutiérrez-Adán Alfonso; Fernández-González Raúl; Pérez-Crespo Miriam; Hourcade Juan D (BMC, 2010)
Abstract Background Before ovulation, sperm-oviduct interaction mechanisms may act as checkpoint for the selection of fertilizing spermatozoa in mammals. Postovulatory mating does not allow the sperm to attach to the oviduct, and spermatozoa may only undergo some selection processes during the transport through the female reproductive tract and/or during the zona pellucida (ZP) binding/penetration. Methods We have induced DNA damage in spermatozoa by two treatments, (a) a scrotal heat treatment (42 degrees C, 30 min) and (b) irradiation with 137Cs gamma-rays (4 Gy, 1.25 Gy/min). The effects of the treatments were analyzed 21-25 days post heat stress or gamma-radiation. Postovulatory females mated either with treated or control males were sacrificed at Day 14 of pregnancy, and numbers of fetuses and resorptions were recorded. Results Both treatments decreased significantly implantation rates however, the proportion of fetuses/resorptions was only reduced in those females mated to males exposed to radiation, indicating a selection favoring fertilization of sperm with unfragmented DNA on the heat treatment group. To determine if DNA integrity is one of the keys of spermatozoa selection after postovulatory mating, we analyzed sperm DNA fragmentation by COMET assay in: a) sperm recovered from mouse epididymides; b) sperm recovered from three different regions of female uterine horns after mating; and c) sperm attached to the ZP after in vitro fertilization (IVF). Similar results were found for control and both treatments, COMET values decreased significantly during the transit from the uterine section close to the uterotubal junction to the oviduct, and in the spermatozoa attached to ZP. However, fertilization by IVF and intracytoplasmatic sperm injection (ICSI) showed that during sperm ZP-penetration, a stringent selection against fragmented-DNA sperm is carried out when the damage was induced by heat stress, but not when DNA fragmentation was induced by radiation. Conclusion Our results indicate that in postovulatory mating there is a preliminary general selection mechanism against spermatozoa with low motility and fragmented-DNA during the transport through the female reproductive tract and in the ZP binding, but the ability of the ZP to prevent fertilization by fragmented-DNA spermatozoa is achieved during sperm-ZP penetration, and depends on the source of damage.